2019
DOI: 10.17728/jatp.2947
|View full text |Cite
|
Sign up to set email alerts
|

Kinetika Perubahan Mutu Minyak Buah Merah (Pandanus conoideus) Hasil Degumming Selama Penyimpanan

Abstract: Kandungan fosfolipid dalam minyak kasar buah merah merupakan masalah utama dalam pengolahannya menjadi berbagai produk pangan, yang dapat dihilangkan melalui proses degumming. Tujuan dari penelitian ini adalah untuk mendapatkan model kinetik perubahan kualitas minyak buah merah hasil degumming (MBMD) selama penyimpanan. MBMD dikemas dalam botol gelap dan disimpan pada suhu 60, 75, dan 90°C selama ± 15 hari untuk dievaluasi kadar air, kadar asam lemak bebas (ALB), bilangan peroksida dan total karotenoid. Peruba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Musafira et al [24], also reported that the moisture content and FFA content of coconut oil increased with increasing storage time [24]. Phenomenon of increasing FFA content during storage at 60°-90 o C also occurs in CRFO ((moisture content from 1.9 % to 4.3 %) [14] and DRFO ((moisture content from 3.9 % to 4.34 %) [15]; where the increasing of FFA in NRFO ((moisture content from 1.29 % to 1.66 %) is lower than DRFO, but higher in CRFO.…”
Section: Changes In Nrfo Quality During Storagementioning
confidence: 88%
See 3 more Smart Citations
“…Musafira et al [24], also reported that the moisture content and FFA content of coconut oil increased with increasing storage time [24]. Phenomenon of increasing FFA content during storage at 60°-90 o C also occurs in CRFO ((moisture content from 1.9 % to 4.3 %) [14] and DRFO ((moisture content from 3.9 % to 4.34 %) [15]; where the increasing of FFA in NRFO ((moisture content from 1.29 % to 1.66 %) is lower than DRFO, but higher in CRFO.…”
Section: Changes In Nrfo Quality During Storagementioning
confidence: 88%
“…Furthermore, it was reported that changes in FFA content and peroxide number of the DRFO also followed the zeroth order reaction, with Ea values of 22416 J/mol °K and 34839 J/mol °K, respectively, while the decrease in carotenoid content followed the first order reaction with Ea 48504 J/mol °K. This indicates that the lowest Ea was found for FFA content so that DRFO is most sensitive to hydrolysis deterioration during storage [15]. What is the oxidation kinetics behavior in NRFO during storage as a function of time.…”
Section: Jurnal Teknologimentioning
confidence: 94%
See 2 more Smart Citations
“…The stability of the samples was analyzed according to Sarungallo et al [19] method with modification. The sensitivity of the samples to the light effect was monitored daily for five days.…”
Section: Stability Analysis Of Omega-3 Concentratementioning
confidence: 99%